Clinical Aspects and Current Evidence Base for Transcatheter Aortic Valve Implantation. Issue 6 (November 2015) - Grunau, Gilat Linn; Blanke, Philipp; Leipsic, Jonathon
Abstract : Aortic stenosis (AS) is a common disorder that affects nearly 5% of individuals over 75 years of age. Many patients with AS are unable to undergo surgical valve replacement (SAVR) as they are commonly deemed to be of very high risk. Transcatheter aortic valve implantation (TAVI), introduced in 2002, is a new method for treatment of these patients. Computed tomography (CT) is becoming the gold standard imaging modality for preprocedural planning, including assessment of annular size and access. Since 2002, >100, 000 procedures have been performed with either a balloon-expandable valve (Edwards SAPIEN valve) or the self-expanding valve (Medtronic CoreValve). A growing body of evidence supporting the effectiveness and safety of TAVI includes the PARTNER trial and the CoreValve pivotal trial. These have found significantly better survival for the TAVI arm compared with SAVR (CoreValve). There were no significant differences in all-cause mortality between TAVI and SAVR, whereas significantly reduced all-cause mortality was observed for TAVI when compared with standard therapy (PARTNER). Paravalvular regurgitation is increased in TAVI compared with SAVR; however, integration of CT into valve selection has shown to improve outcomes. There is conflicting evidence regarding increased risk for stroke after TAVI, and occurrence of conduction disturbances and the need for a pacemaker after TAVI remain a concern. Upcoming trials are focusing on assessing outcomes for use of TAVI in intermediate–operative risk patients. The future will likely include an increased choice of devices, smaller access sites, and further integration of CT for preprocedure planning.